3(2k+18)=6(9+k)

Simple and best practice solution for 3(2k+18)=6(9+k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2k+18)=6(9+k) equation:


Simplifying
3(2k + 18) = 6(9 + k)

Reorder the terms:
3(18 + 2k) = 6(9 + k)
(18 * 3 + 2k * 3) = 6(9 + k)
(54 + 6k) = 6(9 + k)
54 + 6k = (9 * 6 + k * 6)
54 + 6k = (54 + 6k)

Add '-54' to each side of the equation.
54 + -54 + 6k = 54 + -54 + 6k

Combine like terms: 54 + -54 = 0
0 + 6k = 54 + -54 + 6k
6k = 54 + -54 + 6k

Combine like terms: 54 + -54 = 0
6k = 0 + 6k
6k = 6k

Add '-6k' to each side of the equation.
6k + -6k = 6k + -6k

Combine like terms: 6k + -6k = 0
0 = 6k + -6k

Combine like terms: 6k + -6k = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4x^2+56x+156=0 | | s=4s-60 | | 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 | | 3(2g+7m)= | | (x+x)-20x+100=0 | | 0.2r=-8 | | v+53=3v+21 | | 9=5.4*x | | 5y^2+7y-4=0 | | 12-4p=-4(-5p-3) | | (5x-15)=what | | 5y-2=3x+2 | | 4(-2f-6g)= | | 3x=2.52 | | 140=4x^2-4+4-16 | | x^1000=0.9 | | 3y=-x+0 | | 13w+16w-7+5=-5w+5-7 | | 4x^2-156=0 | | 8(-4k-4)=-5k-32 | | 3(3+2j)= | | 3z-35=5z-87 | | 5m-13=n+5 | | u=2u-74 | | x=7x+6y |

Equations solver categories